LEGAL PROTECTION AGAINST THE SALE AND PURCHASE OF LAND UNDER HANDS BASED ON LAW NUMBER 5 OF 1960 CONCERNING BASIC REGULATIONS ON AGRARIAN PRINCIPLES (Study Decision Number:46/Pdt.G/2021/PN Gsk) - Khelvin Yudda Ramadhan; Yuniar Rahmatiar; Suyono Sanjaya (Jurnal Ilmiah Advokasi, 2024)
In accordance with Article 19 of Law No. 5/1960 on the Basic Regulation of Agrarian Principles, the government is also responsible for providing legal certainty in the process of land registration throughout Indonesia in accordance with the regulations stipulated by Government Regulations. It is clear that the buyer in buying and selling land under the hand is entitled to legal protection and can reverse the name of the land certificate that has been purchased, of course, the actions of the heirs in this case are clearly in bad faith because they do not want to split the land certificate whose land has been sold to others.This scientific research uses qualitative research methods in normative juridical. The author uses a normative juridical strategy in this approach. From the results of the research that has been discussed, it can be concluded that the buyer in this case is declared entitled to legal protection, because in the sale and purchase agreement between the buyer and the seller legally and consciously carry out an agreement to sell land. And the actions of the heirs in this case do not want to break the land certificate and change the name of course this can harm the buyer. Article 19 of Law Number 5 of 1960 concerning Basic Agrarian Principles mandates the public to carry out the land registration process with the aim of providing a guarantee of legal certainty in the sale and purchase transactions of land rights.Keywords: Legal protection, Land sale and purchase, Legal certainty